2020
DOI: 10.3389/fonc.2020.536842
|View full text |Cite
|
Sign up to set email alerts
|

Right Compared With Left Thoracic Approach Esophagectomy for Patients With Middle Esophageal Squamous Cell Carcinoma

Abstract: Background: In China, open surgical approaches for esophageal cancer (EC) can be divided into two techniques, the right-and left-transthoracic esophagectomy. Although there is an increasing number of instances that use the right side, the optimal surgical technique remains unclear. Based in a large cancer center with rich experience of both transthoracic side approaches, this study compared the long-term survival of patients treated by these two surgical techniques. Methods: The patients included in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Although right thoracic esophagectomy is more effective than left thoracic esophagectomy for lymph node dissection for esophageal cancer [21][22][23], there is no prospective study evidence whether patients really benefit from radical lymph node dissection and the optimal extent of lymph node removal during esophagectomy still remains unclear [24,25]. Two studies from Sweden and the United Kingdom showed that intraoperative lymph node dissection for esophageal cancer had no significant effect on the survival and prognosis of patients with esophageal cancer [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Although right thoracic esophagectomy is more effective than left thoracic esophagectomy for lymph node dissection for esophageal cancer [21][22][23], there is no prospective study evidence whether patients really benefit from radical lymph node dissection and the optimal extent of lymph node removal during esophagectomy still remains unclear [24,25]. Two studies from Sweden and the United Kingdom showed that intraoperative lymph node dissection for esophageal cancer had no significant effect on the survival and prognosis of patients with esophageal cancer [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…These advantages are supported by solid evidence from large surgical cohorts in northern central China. [18][19][20][21] In fact for operations as traumatic as transthoracic resection of esophageal cancer with 2 or 3 eld lymphadenectomy, surgical complication or postoperative morbidity also affect postoperative survival. [22] In a multivariate Cox regression analysis of 419 esophageal cancer cases resected at Keio University Medical School Hospital of Japan, Ando reported that among the seven signi cant independent prognostic factors including gender, surgical year (1981-1987 vs. 1988-1995), depth of tumor invasion (T1b/T2/T3/T4), lymph node metastasis (N0/N1-3/N4-6/N7-), degree of residual tumor (R0/R1,R2), postoperative complication (none/non-lethal complication/lethal complication) and number of dissected mediastinal nodes, the effect of postoperative complication was the largest and was identical to that of lymph node metastasis (Relative risk and 95% CI 2.23 (1.78-2.80), P<0.0001 and 1.59 (1.34-1.89), P<0.0001 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[24]However, a recent study in a high volume center (Henan Cancer Center) comparing the right (n=202) and left thoracic approach esophagectomy (n=235) found no signi cant difference in 5-year survival rate. [20] The Henan colleagues argued that the left approach as described in the Fudan trial might have been unrepresentative of a standard Sweet approach by experienced hands in high volume centers because the usual advantages in operation time, hospital stay and surgical complication are not apparent as compared to that in other Chinese studies. [18-21,25]Interestingly however, Henan colleagues not only demonstrated the usual advantages concerning surgical safety for the Sweet approach, the median number of lymph node retrieved by them with the left approach was no less than that with the right approach (median 21 (8-64) vs.26 (8-60), P=0.708).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment of esophageal carcinoma has a history of 100 years, and the first esophagectomy was successfully completed by Torek in 1913 (1). As medical science has advanced and our understanding of esophageal carcinoma has improved, esophageal carcinoma surgery has developed from the initial left thoracic approach to the right thoracic approach (2) and to the current minimally invasive esophagectomy (MIE) (3), and the surgical methods continue to improve. Open esophagectomy involves extensive trauma, severe pain, and high complication and mortality rates.…”
mentioning
confidence: 99%